Vertical jump, anaerobic power, and shooting accuracy are not altered 6 hours after strength training in collegiate women basketball players - Woolstenhulme, M. T.; Bailey, B. K.; Allsen, P. E. (The Journal of Strength and Conditioning Research, 2004)
Vertical jump, anaerobic power, and shooting accuracy were measured in 18 Division I women basketball players (age 18-22 years) 6 hours following a morning strength training routine called a lift day (LD) and on a control day in which no strength training was performed. Subjects had been strength trained for 4 weeks prior to testing. The strength training session on lift day was a full-body workout and included 7 exercises performed in 3-6 sets at loads ranging from a 5 to 12 repetition maximum (RM). There were no significant differences in jump height with 2 legs (49.5 ± 4.8 cm and 49.0 ± 4.8 cm, LD and control, respectively), relative mean power output over 30 seconds on a Wingate bicycle test (6.4 ± 0.8 W·kg-1 and 6.6 ± 0.7 W·kg-1, LD and control, respectively), or shooting accuracy over 60 seconds (21.5 ± 3.8 points/min and 21.3 ± 4.1 points/min, LD and control, respectively). These data suggest that in collegiate women basketball players, a previous bout of strength training has no negative effect on vertical jump height, anaerobic power, or shooting accuracy.